Penapisan Bakteri Filosfer Penghasil Senyawa Bioaktif Anti Xanthomonas oryzae pv. oryzae Penyebab Penyakit Hawar Daun Bakteri pada Padi - NURFITRIANI RINA; NI PUTU RATNA AYU KRISHANTI; ALINA AKHDIYA; ARIS TRI WAHYUDI (Jurnal Sumberdaya Hayati, 2016)
Bacterial leaf blight caused by Xanthomonas oryzae pv. oryzae (Xoo) is one of the important diseases in rice crops in Indonesia. The disease is difficult to be controlled since it attacks the rice plant at different growth stages such as tillering, flowering and ripening. One of the alternatives that could be used to control the disease is by using phyllosphere bacteria as the biocontrol agents. This study aims to isolate, characterize and screen the rice phyllosphere bacteria producing bioactive compounds against Xoo. Phyllosphere bacteria isolated from healthy leaves of rice var. Ciherang by using 4 different media obtained 285 bacterial isolates which were consisted of the 65 isolates of King’s B agar, 86 isolates of Nutrient agar, 81 isolates of Luria-Bertani agar, and 53 isolates of Trypticase Soy agar media. Antagonist test using double layer method showed 58 isolates of phyllosphere bacteria produced bioactive compounds that inhibited the growth of Xoo. Pathogenicity test agaist rice leaf revealed 18 bacterial isolates did not perform their potencies as pathogenic bacteria. Among the 18 non-phytopathogenic bacterial isolates, 14 isolates belong to Gram-positive bacteria and 4 isolates belong to Gram-negative bacteria. Five isolates among Gram positive bacteria were predicted as Bacillus genera.